The Impact Of Plyometric Exercises On The Strength Speed And Skillful Performance Of Soccer Players U19 - Tahri , Rabah; Aboura , Rabah (sports creativity, 2025)
The study aimed to know the impact of the plyometric training on the strength of speed and some skills on football players juniors through a special plyometric exercise program, the research sample consisted of control and experimental groups each group contain 14 players, who were chosen in a simple random manner using the experimental method and as tools for the study was used a set of physical and skill tests, the data were statistically processed by spss and Exel program the results yielded indicated the effect of the proposed plyometric exercises on the strength of speed and the skills